Realizing Women's Independence: Assistance for the Empowerment of PKK Mekar Sari Based on Virgin Coconut Oil (VCO) Processing in Padukuhan Karanggede, Kulon Progo - Saputra, Rivaldi Alan; Octaviana, Syva; Adylla, Siti Fatur; Marischa, Diva; Amalia, Intan; Rozaki, Zuhud (Universitas Galuh, 2025)
Women's empowerment is a form of activity to realize social change in a planned manner as a solution to problems or to meet needs in community life. The YSI BEM KM UMY team implies an educational role in empowerment for five months starting from July-November 2022 to the PKK Mekar Sari Jatimulyo Village. Empowering the manufacture of Virgin Coconut Oil (VCO) oil is one of the ways PKK Mekar Sari is independent in realizing a smart and independent women's group. The objectives of empowerment are in the form of; 1) the formation of the Coconut Management Group (KELAPA) which acts as the person in charge of VCO Production; 2) increasing public understanding and independence regarding the use of coconuts into VCO; 3) the community is able to operate centrifugation equipment so that it produces better VCO; 4) the community is able to solve marketing problems so that it makes it easier to sell VCOs. The empowerment method starts from problem identification, conceptualization stage, program implementation, as well as monitoring and evaluation. The results of this empowerment are in the form of; 1) the creation of the Padukuhan Karanggede community who are members of the KELAPA (Coconut Processing Group) organization who have an adequate understanding in making VCO; 2) the creation of the original VCO product of PKK Mekar Sari; 3) centrifugation device as an innovation in the production of VCO oil; 4) and, increasing public understanding related to marketing management science.